Design of an L-Valine-Modified Nanomicelle-Based Drug Delivery System for Overcoming Ocular Surface Barriers - Huimin Wu; Yuchen Xu; Mengru Cai; Longtai You; Jing Liu; Xiaoxv Dong; Xingbin Yin; Jian Ni; Changhai Qu (MDPI AG, 2022)
The incidence of ocular surface disease (OSD) is increasing, with a trend towards younger ages. However, it is difficult for drugs to reach the deep layers of the cornea due to ocular surface barriers, and bioavailability is less than 5%. In this study, DSPE-PEG2000 was modified with L-valine (L-Val), and an HS15/DSPE-PEG2000-L-Val nanomicelle delivery system containing baicalin (BC) (BC@HS15/DSPE-PEG2000-L-Val) was constructed using thin-film hydration, with a high encapsulation rate, small particle size and no irritation to the ocular surface. Retention experiments on the ocular surface of rabbits and an in vivo corneal permeation test showed that, compared with the control, nanomicelles not only prolonged retention time but also enhanced the ability to deliver drugs to the deep layers of the cornea. The results of a protein inhibition and protein expression assay showed that nanomicelles could increase uptake in human corneal epithelial cells (HCEC) through energy-dependent endocytosis mediated by clathrin, caveolin and the carrier pathway mediated by PepT1 by inhibiting the overexpression of claudin-1 and ZO-1 and suppressing the expression of PepT1-induced by drug stimulation. These results indicate that BC@HS15/DSPE-PEG2000-L-Val is suitable for drug delivery to the deep layers of the ocular surface, providing a potential approach for the development of ocular drug delivery systems.